Complications of Ultrasonography Guided Percutaneous Renal Biopsy in Children: A Retrospective Study in a Tertiary Hospital in Nepal (Nepalese Journal of Radiology, 2022)
Introduction:  Percutaneous renal biopsy is done under ultrasonographic guidance in recent times due to which the diagnostic yield has increased and complications have been severely curtailed. We aimed to retrospectively evaluate the complications following kidney biopsy in children.Methods: After obtaining ethical clearance, retrospective evaluation of sixty pediatric renal biopsies done in BPKIHS from October 1, 2018, to September 30, 2020, were included in the study. Biopsies were done by 18G biopsy guns under ultrasound guidance and the complications were evaluated.Results: Of sixty patients, 13.33% had gross hematuria, 3.33% had a perirenal hematoma and the biopsy failure rate was 3.3%. None of the patients required blood transfusion and had major complications requiring further intervention.Conclusions: Percutaneous renal biopsy under ultrasonographic guidance is a safe procedure with a better success rate.